Activating Educational Vouchers in Private Education Schools in the Light of the American Experience, Entrance to the Privatization of Public Education (proposed Concept) - Al-Khudair, Amal Muhammad Ali; Al-Sayari, Nisreen Nasser (Journal of Educational and Psychological Sciences, 2023)
This study aims to present a proposed conception to activate educational vouchers at private schools in the light of American experience as an entrance to privatization of public education after noticing the perceptions of educational experts about the (physical-administrative-procedural) requirements to activate educational vouchers in private schools. To achieve the previous objectives, the study used the descriptive method via Delphi style, which is one of the methods of future studies. The study conducted in two rounds between two groups of (13) experts with an interest in educational vouchers. The study reached several results, perhaps the most prominent of which are: 1. The physical requirements to activate educational vouchers in private schools include the sufficiency of the material value of the educational voucher to cover the cost of basic education services for the beneficiaries, in addition to the variation of the educational voucher’s value for the beneficiaries according to the educational stage. 2. The most prominent administrative requirements to activate educational vouchers in the private schools appears on the submission of clear reports from the school in case of exclusion or cancellation the service for some beneficiaries and continuous follow-up of the service’ quality provided for the beneficiaries. 3. The most important procedural requirements to activate educational vouchers in the private schools are the periodical evaluation of the facilities of private schools, the adequacy of their equipment, and educational means, in addition to identifying and announcing the institutional evaluation criteria for private schools as they are specialized and receive government support. Considering that, the study presents a proposed conception to activate educational vouchers in the private schools in light of the American experience as an entrance to privatization of public education with contemporary starting points and practices that employing global expertise.